Physicians as Executives: Opportunities and Strategies for Health-System Pharmacy Leaders - Harvin, Andre (Hosp Pharm, 2014)
To deal with the pressures in health care that stress clinical excellence and profitability, health systems are increasingly recruiting physician executives or physicians in leadership and management positions. Physicians occupy less than 5% of all hospital leadership positions, but there is an apparent increase in the recruitment of physician executives. With the growth in the number of physician executives, pharmacy leaders must capitalize on their existing clinical relationship and apply it to health care leadership and management. By focusing on developing an executive presence, by clearly describing a patient-centered strategy and vision for pharmacy, and by nurturing the existing clinical relationships, the pharmacy director can work with physician executives to promote patient-centered pharmacy services.